The Dynamics of Mandailing Society in the Development of Maktab Islamiah Tapanuli in Medan (1917-1947) - Jufri Naldo; Muhammad Rezki Lubis (Yupa: Historical Studies Journal, 2023)
This article analyzes the dynamics of the Mandailing community during the development of the Tapanuli Islamic College. The focus of this study lies in explicating the historical traces of the formation of Islamic Maktab, the Al Washliyah organization, and the contribution of the Mandailing community to the development of these institutions. This research employs a qualitative research approach, utilizing historical research methods. Historical research involves four stages: heuristics, source criticism, interpretation, and historiography. Regarding the type of study, this paper falls under the domain of social history, examining the Mandailing community as a social group and the Islamic College as a social institution. The conducted research has yielded several conclusions. Firstly, the Mandailing community played a crucial role in advancing Islamic Colleges and made significant progress in the socio-religious sphere, notably exemplified by establishing the Al Washliyah organization. Secondly, the part of the Mandailing community can be observed in their accommodating nature, as demonstrated through various social activities.